2000
DOI: 10.1002/(sici)1096-9861(20000103)416:1<79::aid-cne6>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cortex on the human posterior superior temporal gyrus

Abstract: The human superior temporal cortex plays a critical role in hearing, speech, and language, yet its functional organization is poorly understood. Evoked potentials (EPs) to auditory click‐train stimulation presented binaurally were recorded chronically from penetrating electrodes implanted in Heschl's gyrus (HG), from pial‐surface electrodes placed on the lateral superior temporal gyrus (STG), or from both simultaneously, in awake humans undergoing surgery for medically intractable epilepsy. The distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
250
1
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(282 citation statements)
references
References 78 publications
24
250
1
2
Order By: Relevance
“…Strongest cortical currents (visualized in blue color) were observed in and close to left pSTG/MTG. cortex, both with respect to its functional an anatomical properties (Howard et al, 2000).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Strongest cortical currents (visualized in blue color) were observed in and close to left pSTG/MTG. cortex, both with respect to its functional an anatomical properties (Howard et al, 2000).…”
Section: Discussionmentioning
confidence: 63%
“…1 B). Based on the known neuroanatomy of the auditory system (Howard et al, 2000), the temporal plane comprises primary and secondary auditory cortex whereas the neighboring areas in superior and middle temporal gyri encompass auditory association areas. The MR signal was generally higher to real sounds than to acoustic noise in the temporal plane and in superior temporal cortex.…”
Section: Fmri Experiments 2: Perceptual Taskmentioning
confidence: 99%
“…The results of this study confirm previously reported intracranial findings that the presentation of brief tones produces a strong, multiphasic response in the human perisylvian area (Celesia, 1976;Richer et al, 1989;Liégeois-Chauvel et al, 1994;Halgren et al, 1995;Howard et al, 2000;Rosburg et al, 2004;Edwards et al, 2005). Lateral surface recordings from the temporal lobe in the present patients exhibited the largest negative peak in the averaged ERP waveform over the upper bank of the STG or the SF, with the maximal recording site more likely to occur over the SF as ISI decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Evoked responses in PAC of Heschl's gyrus (HG) had response latencies ranging from 15 to 25 ms, which are compatible with the magnetoencephalography (MEG) data on click latency in PAC reported by Lü tkenhö ner et al (2003). Then, when this region of HG was electrically stimulated, it resulted in an evoked potential in PLST (Howard et al 2000;Brugge et al 2003). The average onset latency for this evoked response was only 2.0 ms, consistent with an ipsilateral corticocortical connection between HG and PLST.…”
Section: A Brief Overview Of Auditory Anatomy (A)mentioning
confidence: 90%